Literature Study Analysis of the Effect of the Problem-Based Learning Model on Critical Thinking and Problem-Solving Skills - Jumiah Jumiah; Jeklin Hutagaol (Universitas Ahmad Dahlan, 2025)
Learning at school requires students to be able to develop their own learning skills, including critical thinking skills and problem-skills. Students will get various values that will bring changes to student actions. The research aims to re-analyze the effect of the PBL learning model on students' learning skills in biology learning. This research is a study that uses literature study techniques with a sample of 12 national journal articles and 4 international journal articles to be analysed. This journal article will show the effect size of each article that has been obtained will then be interpreted according to the effect size classification. The results of this study show that the effect size of students' learning skills on the average effect size of critical thinking skills is 1.56 and problem-solving skills is 1.22. In this study it can be concluded that the results of the meta-analysis show that there is an influence of the problem-based learning model on student learning skills.